Orthostatic Hypotension in Parkinson's Disease: The Relation of Blood Pressure Tests and Symptoms in Daily Life - Velseboer, Daan C. (Mov Disord Clin Pract, 2016)
BACKGROUND: Orthostatic hypotension (OH) is common in Parkinson's disease (PD), but the relation between the results of orthostatic blood pressure tests and orthostatic symptoms in daily life is not clear. METHODS: We performed a cross‐sectional study in an incident nontertiary care cohort of PD patients with additional recruitment of PD patients from our own outpatient clinic. We recruited sex‐ and age‐matched controls. All participants underwent orthostatic blood pressure tests using continuous blood pressure measurements. Orthostatic symptoms experienced in daily life were assessed using autonomic symptom questionnaires (SCOPA‐AUT and COMPASS‐31). RESULTS: A total of 83 PD patients and 35 controls were included. Mean patient age was 69.2 years (standard deviation [SD]: 10.0). Mean disease duration was 6.6 years (SD, 0.8). The estimated prevalence of OH in PD was 24.1% (95% confidence interval: 16.2–34.3). There was no significant difference between PD patients with and without OH regarding reported daily orthostatic symptoms. Alternative OH criteria did not substantially improve this. CONCLUSIONS: Perceived orthostatic symptoms in daily life have no clear association with the results of a single orthostatic blood pressure test. Better diagnostic strategies are needed.